Between- and within-site variation in medication choices and adverse events during procedural sedation for electrical cardioversion of atrial fibrillation and flutter. Issue 3 (7th June 2017) - Clinkard, David; Stiell, Ian; Lang, Eddy; Rose, Stuart; Clement, Catherine; Brison, Robert; Rowe, Brian H.; Borgundvaag, Bjug; Langhan, Trevor; Magee, Kirk; Stenstrom, Rob; Perry, Jeffery J.; et al.
ABSTRACT: Objectives: Although procedural sedation for cardioversion is a common event in emergency departments (EDs), there is limited evidence surrounding medication choices. We sought to evaluate geographic and temporal variation in sedative choice at multiple Canadian sites, and to estimate the risk of adverse events due to sedative choice. Methods: This is a secondary analysis of one health records review, the Recent Onset Atrial Fibrillation or Flutter-0 (RAFF-0 [n=420, 2008]) and one prospective cohort study, the Recent Onset Atrial Fibrillation or Flutter-1 (RAFF-1 [n=565, 2010 – 2012]) at eight and six Canadian EDs, respectively. Sedative choices within and among EDs were quantified, and the risk of adverse events was examined with adjusted and unadjusted comparisons of sedative regimes. Results: In RAFF-0 and RAFF-1, the combination of propofol and fentanyl was most popular (63.8% and 52.7%) followed by propofol alone (27.9% and 37.3%). There were substantially more adverse events in the RAFF-0 data set (13.5%) versus RAFF-1 (3.3%). In both data sets, the combination of propofol/fentanyl was not associated with increased adverse event risk compared to propofol alone. Conclusion: There is marked variability in procedural sedation medication choice for a direct current cardioversion in Canadian EDs, with increased use of propofol alone as a sedation agent over time. The risk of adverse events from procedural sedation during cardioversion is low but not insignificant. We did not identify an increased risk of adverse events with the addition of fentanyl as an adjunctive analgesic to propofol. RÉSUMÉ: Objectifs: Bien que le recours à la sédation interventionnelle soit chose courante au service des urgences (SU), il existe peu de données sur le choix des médicaments. Aussi avons-nous tenté d'évaluer les différences géographiques et temporelles quant aux choix des sédatifs dans plusieurs centres au Canada, et d'estimer le risque d'événement indésirable lié au choix des sédatifs. Méthode: Il s'agit d'une analyse secondaire d'un examen de dossiers médicaux, le Recent Onset Atrial Fibrillation or Flutter-0 (RAFF-0 [n=420; 2008]), ainsi que d'une étude de cohorte, prospective, la Recent Onset Atrial Fibrillation or Flutter-1 (RAFF-1 [n=565; 2010-2012]), menés respectivement dans huit et dans six SU, au Canada. Les choix des sédatifs ont été quantifiés entre les SU et dans les SU eux-mêmes, et les risques d'événement indésirable, examinés à l'aide de comparaisons rajustées et non rajustées entre différents schémas posologiques de sédatifs. Résultats: Dans le RAFF-0 et la RAFF-1, l'association de propofol et de fentanyl était le schéma le plus fréquent (63, 8 % et 52, 7 %), suivi du propofol seul (27, 9 % et 37, 3 %). Il y avait sensiblement plus d'événements indésirables relevés dans la base de données du RAFF-0 (13, 5 %) que dans celle de la RAFF-1 (3, 3 %). Toutefois, dans les deux bases de données, la mixtion de propofol et de fentanyl n'a pas été associée à un risque accru d'événement indésirable comparativement au propofol seul. Conclusion: Il existe des différences importantes entre les SU, au Canada, quant aux choix des médicaments utilisés pour les sédations interventionnelles en vue des cardioversions électriques, et l'emploi du propofol seul comme agent de sédation a gagné du terrain au fil du temps. Le risque d'événement indésirable découlant de la sédation interventionnelle durant la cardioversion est faible, mais non insignifiant. D'après les résultats de l'étude, l'adjonction de fentanyl au propofol, comme analgésique, n'est pas associée à un risque accru d'événement indésirable.